Unlocking the Future: Navigating the World of Cryptocurrency Investments. - Ballada, Tzietle A; Camacho, Mark John G; Dumaguin, Maria Fatima M; Panelo, Mark Justine B; Hanna Faith M (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Cryptocurrency is a digital or virtual form of money secured by cryptography, which makes it nearly impossible to counterfeit or double-spend. Familiarity with cryptocurrency empowers individuals to navigate the evolving landscape of digital finance and participate in its potential for innovation and growth. This study determines the unlocking future, navigating the world of cryptocurrency investments. A quantitative descriptive method and correlational research design was utilized, gathered data using researcher administered survey questionnaires to find out the level of familiarity and perceptions of employed workers on cryptocurrency, around the central business district of the City of San Fernando, La Union. However, the findings indicate that while there is a notable level of familiarity with cryptocurrency among participants, the majority are still unfamiliar with it. Interestingly, a significant portion express interest in investing in cryptocurrency, although nearly half do not. Overall, there appears to be a growing positive inclination towards cryptocurrency investment.